ANALISIS PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI : PERBANDINGAN EMPAT MODEL PREDIKSI (Model Springate’s, Model Model Zmijewski, Model Taffler Dan Model Altman Z-Score) - Siti Maisyarah Sakmah; Slamet Haryono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of conducting this research is a first step to find out the difference in model bankruptcy prediction in manufacturing sector companies with several models of bankruptcy analysis namely springate model model, Zmijewski model, Taffler model and Altman Z-Score model, and researchers will try to do an analysis of bankruptcy calculation, in order to provide a result that shows the most appropriate bankruptcy prediction model for the accuracy of the four models. this study tried to test existing manufacturing companies in IDX with a research period starting from 2015-2019. Data calculations are used with data analysis techniques in accordance with the formula of each ratio in accordance with the bankruptcy prediction model used by researchers. The results showed that there was a difference from each bankruptcy prediction using the Springate model, Zmijewski model, Taffler model and Altman model. And there are three bankruptcy prediction models that have a high accuracy rate of 100% namely the Springate model, Taffler Model and Altman model. While the Zmijewski model has a low level of accuracy compared to others. Keyword: Bankruptcy, Model Springate, Model Zmijewski, Model Taffler and Model Altman Z-Score